Pengaruh Biaya Operasional, Pendapatan Operasional, Non Performing Financing dan Financing to Deposit Ratio terhadap Return on Asset - Muthi'ah Afifah Fauziah; Nana Diana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to examine the effect of BOPO, NPF, and FDR on Profitability described by ROA at Islamic Commercial Banks registered with OJK for the 2016-2020 period. Sampling using purposive sampling and obtained 7 Islamic Commercial Banks that meet the criteria of 14 Islamic Commercial Banks as a sample. So the number of samples studied is 35 data for 5 years. This research method uses quantitative methods. The approach used in this study is a descriptive and verification approach. Based on the results of research conducted using SPSS 20, it can be concluded both partially and simultaneously, namely. BOPO has a negative and significant effect on return on assets, NPF has a positive and significant effect on return on assets and FDR has a positive and significant effect on return on assets while simultaneously BOPO, NPF, FDR have a significant effect on return on assets in Islamic commercial banks in Indonesia Registered at OJK for the 2016-2020 period. In this study, it shows that the variables studied, namely BOPO, NPF and FDR, can describe 92.6% of Return On Assets (ROA). Keywords: BOPO, NPF, FDR, ROA